Dual mode of IFI16 binding to supercoiled and linear DNA: A closer insight - Valková, Natália; Kratochvilová, Libuše; Martinková, Lucia; Brázda, Václav (Biochemical and biophysical research communications, 2023)
IFI16 (Interferon inducible protein 16) is a DNA sensor responsible for innate immune response stimulation and a direct viral restriction by modulating gene expression and replication. Many IFI16-DNA binding properties were described - length-dependent and sequence-independent binding, oligomerization of IFI16 upon recognition, sliding on the DNA, and preference for supercoiled DNA. However, the question of the role of IFI16-DNA binding in distinct IFI16 functions remains unclear. Here we demonstrate two modes of IFI16 binding to DNA using atomic force microscopy and electrophoretic mobility shift assays. In our study, we show that IFI16 can bind to DNA in the form of globular complexes or oligomers depending on DNA topology and molar ratios. The stability of the complexes is different in higher salt concentrations. In addition, we observed no preferential binding with the HIN-A or HIN-B domains to supercoiled DNA, revealing the importance of the whole protein for this specificity. These results provide more profound insight into IFI16-DNA interactions and may be important in answering the question of self- and non-self-DNA binding by the IFI16 protein and potentially could shed light on the role of DNA binding in distinct IFI16 functions.
Keywords: G-quadruplex; DNA; Immunity, Innate; Inverted repeat; IFI16; AFM; fosfoproteiny; superhelikální DNA; DNA, Superhelical; Phosphoproteins; přirozená imunita; Superhelicity